Life cycle analysis of nanoparticles : risk, assessment and sustainability - Vaseashta, A. (DEStech Publications, Inc., 2015)
Addresses the ways life cycle assessment (LCA) concepts can be applied to analyse the fate of nanoparticles in a variety of environmental and manufacturing settings. After introducing LCA theory and modelling concepts, the work discusses risks associated with carbon nanotubes, graphene, silver, fullerenes, iron oxides and other particles.